PELAKSANAAN EVALUASI KURIKULUM DI SDN 1 JENGGIK UTARA - Muh Miftahurrazikin; Tria Marvida; Siti Ghaida Sri Afira Ruhyadi; Wildan Nuril Ahmad Fauzi (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
Evaluation of curriculum implementation can be carried out internally and externally. In this study, the authors want to examine how the process of implementing the evaluation at SDN 1 Jenggik Utara. SDN 1 Jenggik Utara is one of the basic education institutions at the SD/MI/Equivalent level that carries out regular and routine evaluations to ensure the quality of the institution. The researcher uses the type of case study research. The research instrument used is the interview guide. Data collection techniques using interviews and observation. The data analysis technique uses data reduction, data display, and drawing conclusions. The results showed that the implementation of the 2013 curriculum at SDN1 Jenggik Utara was not carried out properly, this was due to several factors such as the ability of teachers to implement K-13-based learning and the lack of facilities and infrastructure at the school.